2019
DOI: 10.1080/20786190.2019.1596665
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of general practitioners on National Health Insurance in Chris Hani district, Eastern Cape, South Africa

Abstract: Background: National Health Insurance (NHI) intends to provide universal health coverage to all South Africans, with equity and quality as its tenets. The participation of private general practitioners (GPs) in NHI is essential. The aim was to explore perceptions of GPs on NHI in Chris Hani district, Eastern Cape, South Africa. Methods: A descriptive phenomenological qualitative study using semi-structured individual interviews of 12 GPs from six municipalities was undertaken. Data analysis used the framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Detailed exploration and piloting of provider payment methods by the NHI task team at the National Department of Health is needed to find options that will encourage GPs to participate in the NHI. Future research may be able to quantify the issues explored in this and other studies 23,25 through a national descriptive survey of GPs.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed exploration and piloting of provider payment methods by the NHI task team at the National Department of Health is needed to find options that will encourage GPs to participate in the NHI. Future research may be able to quantify the issues explored in this and other studies 23,25 through a national descriptive survey of GPs.…”
Section: Discussionmentioning
confidence: 99%
“…The current system is constructed of two tiers, i.e., the private sector and public sector. The majority of financial and human resources lie within the private sector which services ~ 16% of the population, whereas the public sector services ~ 84% of the population [ 3 , 4 ]. The country’s healthcare profile faces a quadruple burden of disease, resulting in significant strain on the public healthcare sector.…”
Section: Introductionmentioning
confidence: 99%
“…In his study in the Western Cape, Valley 12 highlighted poor communication between the provincial health department and the private GPs as a primary concern. In a recent study of GP perceptions towards NHI in the Chris Hani District, Gaqavu and Mash 13 reported GP uncertainty around the government’s capacity to implement the policy and implications for solo GPs. The GPs also voiced a need for more information and engagement by government.…”
Section: Introductionmentioning
confidence: 99%